Consumer Anxiety Management Strategies on Purchasing Decision Making Against the Impact of Digital Advertising In the E-Commerce Era - Rundika Pratiwi, Endah (Asosiasi Ahli Administrasi Indonesia, 2025)
The e-commerce era has fuelled the rise of persuasive and aggressive digital advertising, influencing the way consumers make purchasing decisions. This study aims to identify the strategies used to manage anxiety triggered by exposure to digital advertising. A qualitative approach was used with data collection techniques through in-depth interviews and focus group discussions with six informants who actively shop on e-commerce platforms. The results show that consumers experience various forms of anxiety, such as fear of running out of products, regret for not buying immediately, and social pressure due to the Fear of Missing Out (FOMO) phenomenon. The main cause of anxiety comes from digital advertising elements such as time countdowns, limited stock, celebrity testimonials, and bulk purchase notifications. To manage anxiety, consumers use active, interactive, and passive strategies. The conclusion is that emotional control and awareness are very important in dealing with psychological distress caused by online advertising. The theoretical implications of this research enrich the application of Uncertainty Reduction Theory in the context of digital consumer behaviour, particularly in understanding active, interactive, and passive strategies as a form of uncertainty management accompanied by emotional anxiety. Practically, the findings provide insights for e-commerce industry players and advertisers to be wiser in designing advertising communication strategies by considering the psychological impact on consumers.